Spectroscopic evaluation of the efficient deproteinization process of white shrimp (L. Vannamei) waste for protein-rich hydrolysate applications - Muhammad Reza; Inayah Syahbana; Putri Khofifah Gianto; Achmad Sjaifullah; Istiqomah Rahmawati (Case Studies in Chemical and Environmental Engineering)
This study demonstrated a deproteinization of white shrimp waste using the autolysis method. The deproteinization process was initially carried out using an acidic water solution (pH ∼ 2.5) for 3 or 5 d. The obtained filtrate was then used to incubate another fresh shrimp waste for several cycles using parameters similar to the initial stage. A significant increase in filtrate protein content was observed, which agreed with the UV–Vis spectroscopy results. UV–Vis spectra revealed the considerable effect of filtrate usage on the rise of tryptophan content in the hydrolysate, which was indicated by the increase of peak area at around 290 nm. The highest protein content was 12.49 ± 0.0004 % obtained in filtrate day 15 (FD15). On the other hand, the total nitrogen content of the obtained residue decreased. Infrared spectra confirmed the disappearance of several functional groups (N–H and CO) from the residue. This can be indicated by the significant decrease of the A1621/A1111 value, representing the loss of CO peptide groups in the protein. FTIR spectra of the obtained residue showed mainly the structure of chitin, and it became cleaner when filtrate was used as an incubator solution. The method applies the concept of sustainability and plays a vital role in reducing water use and preserving groundwater.